DEVELOPMENT OF WEB-BASED WORD CARD MEDIA WORDWALL FOR PRACTICING BEGINNING READING SKILLS CLASS I SDN NO. 105321 QUIZ BARACADEMIC YEAR 2023/2024 - Lestari, Dwi; Ramadhani, Mastari; Putri, Nizmi (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2024)
This research was conducted based on observations carried out by researchers at SDN 105321 Batang Kuis. During the observation, the researchers discovered a problem, namely the students' low reading ability. Based on the results of interviews conducted with homeroom teachers regarding students' reading abilities, it was found that students' reading abilities were still low, with many students unable to recognize letters. This is attributed to the limited media available for use in learning and the fact that many students did not go through early childhood education before continuing their elementary school education. This research aims to develop word card media for initial reading material for grade I elementary school students. The study employs the Research and Development (R&D) method. The results of the research show that the word card media is declared suitable for use as a learning medium, with an assessment percentage from media experts of 99.9% and an assessment percentage from material experts of 90.6%. These percentages indicate a very good category from the feasibility test assessment by both media and material experts. Furthermore, the results of the research conducted on 27 students received an assessment carried out by the homeroom teacher as an observer during the field trial process. This assessment yielded a percentage of 95%, which falls into the very good category. The word card media was deemed suitable for use as a learning medium and was able to improve students' reading abilities..